ANALYSIS OF FINANCIAL PERFORMANCE BEFORE AND DURING THE COVID-19 PANDEMIC - Ningsih, Indah Aprilia; Subadriyah, Subadriyah (Stability: Journal of Management and Business, 2023)
This study aims to find out how the differences in the financial performance of the Healthcare sector companies listed on the Indonesia Stock Exchange before and after the entry of covid-19 in Indonesia. The financial performance includes net profit margin, current ratio, debt to equity ratio, and total asset turn over. The type of research used is quantitative. The population used is healthcare companies listed on the Indonesia Stock Exchange in 2017-2020 with a purposive sampling technique so that 40 data are obtained. The data analysis technique used is descriptive data analysis technique, paired sample test and Wilcoxon. The results of this study indicate that the net profit margin, debt to equity ratio, and total asset turnover have no difference before and when Covid-19 entered Indonesia. Meanwhile, the current ratio has a difference between before and when Covid-19 entered Indonesia.